2022
DOI: 10.3390/rs14102469
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Broad-Leaved Tree Crown Based on UAV Visible Images and OBIA-RF Model: A Case Study for Chinese Olive Trees

Abstract: Chinese olive trees (Canarium album L.) are broad-leaved species that are widely planted in China. Accurately obtaining tree crown information provides important data for evaluating Chinese olive tree growth status, water and fertilizer management, and yield estimation. To this end, this study first used unmanned aerial vehicle (UAV) images in the visible band as the source of remote sensing (RS) data. Second, based on spectral features of the image object, the vegetation index, shape, texture, and terrain fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 77 publications
0
8
1
Order By: Relevance
“…Moreover, in a related study by Yang et al [48], the effectiveness of Random Forest (RF) and Support Vector Machine (SVM) in land cover classification was emphasized. Yang et al [48] highlighted RF's robustness and SVM's ability to handle complex feature spaces, in line with our observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a related study by Yang et al [48], the effectiveness of Random Forest (RF) and Support Vector Machine (SVM) in land cover classification was emphasized. Yang et al [48] highlighted RF's robustness and SVM's ability to handle complex feature spaces, in line with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a related study by Yang et al [48], the effectiveness of Random Forest (RF) and Support Vector Machine (SVM) in land cover classification was emphasized. Yang et al [48] highlighted RF's robustness and SVM's ability to handle complex feature spaces, in line with our observations. They also pointed out that compared with Pixel-Based (PB) classification, the Object-Based image analysis (OBIA) method, as Yang et al [48] indicated, can extract features of each element of remote sensing images, providing certain advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Our research primarily centered on evaluating the impacts of various feature extraction methods and their combinations within the context of a single classifier. For example, Yang et al [50] conducted a comparison between the RF method and other widely-used ML classification algorithms, demonstrating that the RF method yielded superior classification results compared to the decision tree, support vector machine, and naive Bayesian methods. Reference [47] reported that the combination of FFT and the RF method exhibited exceptional pothole detection capabilities, achieving an accuracy rate as high as 96.5%, aligning with our study's findings.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, too much feature information can lead to redundancy. Yang K et al [ 11 ] demonstrated that differences in feature dimensionality and importance are the main factors contributing to variation in olive tree extraction accuracy; Guo Q et al [ 12 ] compared different feature combination schemes and showed that the combination by feature elimination had the highest accuracy in urban tree classification. Object-oriented approaches are often combined with machine learning in the selection of classification algorithms.…”
Section: Introductionmentioning
confidence: 99%